Ziauddin Sardar’s Critism of Modern Science - Arif, Syamsuddin; Bey, Shanaz Nurzaini (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: The difference between modern Western science and Islamic science has differency from various aspects to produce several problems in the ontological field, axiological field, and epistemological field. A Pakistani-born scholar in the field of science, Ziauddin Sardar came up with an idea and movement to present Islamic science. This paper is written using the analytical-descriptive method, which analyzes and describes the weaknesses and shortcomings of modern western science against the needs of society, especially Muslims. The purpose of this paper is to reveal the problems of modern science and how Ziauddin Sardar’s arguments and opinions on modern science. So that this paper produces a breakthrough in the integration of science by Ziauddin Sardar who tries to balance Western science with Islamic science that suits the needs of Muslims, and Islamic science whose scope is broad to all humanity and its civilization.